Eastern king prawn Penaeus plebejus stock enhancement—Genetic evidence that hatchery bred prawns have survived in the wild after release - Premachandra, H. K. A.; Becker, Alistair; Taylor, Matthew D.; Knibb, Wayne (Frontiers in Genetics, 2022)
Eastern king prawn (Penaeus plebejus) is endemic to eastern Australia and is of high commercial and recreational value. As part of a recreational fisheries enhancement initiative, hatchery reared juveniles from Queensland were released into two, more southern New South Whales (NSW) estuaries between 2014 and 2015. Responsible stock enhancement programs rely on knowledge of the population structure of the released species. Previously, in consideration of fisheries data, it was assumed the king prawn populations in Australia are one single breeding stock. In the present study, our first aim was to test this posit of no genetic differentiation using mtDNA control region (mtCR) sequences from the wild samples collected from four estuaries ranging from Queensland/ NSW border (source of the stocked animals) to southern NSW. The second objective was to test for signals of hatchery-released animals in the two stocked estuaries. All four surveyed populations had an extremely high level of haplotype diversity (average h = 99.8%) and low level of haplotype sharing between populations. Estimates of PhiPT values were < 0.01 or close to zero and AMOVA test did not indicate any significant differences among populations. Further, phylogenetic analysis and principal coordinate analysis did not support division of samples by population. Collectively these results suggest that eastern king prawn populations along the NSW coast can be considered as a single stock and stocking from the Queensland samples will not necessarily impact the genetic composition of the overall stock. After stocking of two estuaries, sharing of haplotypes was moderate to very high in the stocked sites (>80% in some collections) but negligible in the two unstocked estuaries (≤2%, which is assumed to be background coancestry unrelated to the hatchery). Moreover, some haplotypes present in the hatchery broodstock were detected in stocked sites, but not in unstocked sites. The highest stocking signal was detected in the estuary which becomes isolated from the sea by sand barrier suggesting such “lakes” maybe more favourable for stocking than estuaries directly open to the sea. Findings in the current study should assist in designing and implementation of future prawn stocking programs.